Tension between the corporate and collegial cultures of Australian public universities: The current status - Christopher, Joseph (Academic Press, 2012)
Australian public universities have been under the influence of a corporate management culture since the 1980s. Driven by pressures for more accounting and accountability, its characteristics have variously been described as being in tension with the traditional collegial and autonomous management culture, threatening its demise. This study applies a multi-theoretical lens to recognize the interests of academics as important stakeholders and critically analyses the existing literature to determine the current status of both cultures within Australian public universities. A series of interviews with a number of vice chancellors and other senior management staff complement and provide a management perspective to the analysis. The results suggest that amidst a shift toward a corporate culture, aspects of collegial and autonomous practices continue to exist in various degrees among universities due to different levels of influencing forces on its operating environment. A quasi-management approach exists with continued tensions between both cultures, compromising their expected outcomes. Universities are attempting to narrow this tension gap. An analysis of the quasi-management approach further reveals that a right balance between both cultures has potential to serve as an effective management model under a multi-theoretical platform. The findings provide avenues for further research to examine this potential.